Behavioral economics: the essence and stages of formation - L. N. Drogobytsky (Стратегические решения и риск-менеджмент)
At the turn of the millennia appeared, and in subsequent years, a conceptually new economic theory-the behavioral economy-was significantly entrenched. As all new, it caused some suspicion and opposition of the scientific economic community. This article aims to at least somehow reduce the detrimental impact of these trends. It examines the origins, main actors and a long history of the development of the behavioral economy. At the same time, the essence of its main provisions is revealed, their transformation in time and prospects for practical application are analyzed.